2012
DOI: 10.1242/dev.074500
|View full text |Cite
|
Sign up to set email alerts
|

Control of neuronal cell fate and number by integration of distinct daughter cell proliferation modes with temporal progression

Abstract: SUMMARYDuring neural lineage progression, differences in daughter cell proliferation can generate different lineage topologies. This is apparent in the Drosophila neuroblast 5-6 lineage (NB5-6T), which undergoes a daughter cell proliferation switch from generating daughter cells that divide once to generating neurons directly. Simultaneously, neural lineages, e.g. NB5-6T, undergo temporal changes in competence, as evidenced by the generation of different neural subtypes at distinct time points. When daughter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 54 publications
8
86
1
Order By: Relevance
“…These regulators exert their roles by regulating the key cell cycle genes (Baumgardt et al, 2014). In addition, the canonical Notch pathway was also found to be important for the type I>0 switch, via regulation of all four key cell cycle genes (Ulvklo et al, 2012;Bivik et al, 2015Bivik et al, , 2016. Notch signaling is initially off in NBs -a prerequisite for establishment of NB cell identity in the neuroectoderm -but is gradually activated during lineage progression (Ulvklo et al, 2012;Bivik et al, 2016).…”
Section: /P27mentioning
confidence: 99%
See 1 more Smart Citation
“…These regulators exert their roles by regulating the key cell cycle genes (Baumgardt et al, 2014). In addition, the canonical Notch pathway was also found to be important for the type I>0 switch, via regulation of all four key cell cycle genes (Ulvklo et al, 2012;Bivik et al, 2015Bivik et al, , 2016. Notch signaling is initially off in NBs -a prerequisite for establishment of NB cell identity in the neuroectoderm -but is gradually activated during lineage progression (Ulvklo et al, 2012;Bivik et al, 2016).…”
Section: /P27mentioning
confidence: 99%
“…These three basic proliferation modes have been described in many animal species, and in Drosophila they are referred to as type 0, type I and type II, respectively (Bello et al, 2008;Boone and Doe, 2008;Bowman et al, 2008;Baumgardt et al, 2014;Bertet et al, 2014). The control of alternate daughter proliferation is of profound importance because it can act to expand the number of neurons/glia generated at a certain temporal stage in a developing lineage (Ulvklo et al, 2012). It may furthermore act to control overall cell number in different regions of the developing nervous system, and might even act to modify its basic structure (Kriegstein et al, 2006;Fish et al, 2008;Nonaka-Kinoshita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as mentioned, previous studies have suggested links between Paf1C and Notch target genes e.g., the HES genes [235,236], and we know that Notch is critical for NB division type I>0 switch [167,254]. Hence, we tested the level of E(spl)-HLHm8 i.e., a core player in Notch signaling of developing CNS [167], to detect a putative relation between Ctr9 and Notch.…”
Section: Ctr9 a Key Components Of Paf1cmentioning
confidence: 91%
“…This was identified in the lineages NB5-6T, NB3-3A and NB7-3A, and is critical for correct lineage progression and consequentially VNC development [71,110,[165][166][167]. All of these three types of division modes have also been observed in the developing mammalian brain [161], which suggests that fundamental molecular aspects of alternate daughter proliferation have been conserved throughout evolution [5,168].…”
Section: Nb Division Type Modesmentioning
confidence: 96%
See 1 more Smart Citation